2006
DOI: 10.1016/j.bbamem.2006.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of antimicrobial peptides in planar film systems

Abstract: Planar systems--monolayers and films--constitute a useful platform for studying membrane-active peptides. Here, we summarize varied approaches for studying peptide organization and peptide-lipid interactions at the air/water interface, and focus on three representative antimicrobial membrane--associated peptides-alamethicin, gramicidin, and valinomycin. Experimental data, specifically surface pressure/area isotherms and Brewster angle microscopy images, provided information on peptide association and the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
52
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 79 publications
9
52
0
Order By: Relevance
“…This value is in good agreement with the area for Alm molecule oriented with its helical axis parallel to the interface (S state). These results are consistent with the literature which reported that Alm is immiscible with phospholipids in monolayers spread at the air/water interface and the Alm molecules are oriented with axis of the helix parallel to the interface (3,31,32).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This value is in good agreement with the area for Alm molecule oriented with its helical axis parallel to the interface (S state). These results are consistent with the literature which reported that Alm is immiscible with phospholipids in monolayers spread at the air/water interface and the Alm molecules are oriented with axis of the helix parallel to the interface (3,31,32).…”
Section: Resultssupporting
confidence: 83%
“…AMPs are biocidally active against Gramnegative and Gram-positive bacteria, fungi, enveloped viruses, eukaryotic parasites, and even tumor cells (3). Importantly, AMPs are effective against strains of antibiotic-resistant bacteria (2).…”
mentioning
confidence: 99%
“…By far the most literature can be found for the membraneactive peptides alamethicin, valinomycin and gramicidin [166][167][168][169][170][171][172]. The last was also used to determine the fluidity of the lipid membrane and as a molecular force probe [173,174].…”
Section: Membrane-active Peptides and Integral Membrane Proteinsmentioning
confidence: 99%
“…Most of their AMPs had minimal interaction with zwitterionic lipids, however a few exceptions indicated that electrostatic interactions are not the only attraction between cationic AMPs and negatively charged bacterial membranes. Planar lipid films have also been used combined with Brewster angle microscopy (BAM) to image the interaction of several AMPs with monolayers (Volinski et al, 2006). While two AMPs were immiscible in 1:1 ratios of peptide:DMPC, valinomycin showed phaseseparation in the monolayer.…”
Section: Antimicrobial Peptides: Monolayermentioning
confidence: 99%
“…Thus, phospholipid-PDA systems could be used, especially in conjunction with BAM, to elucidate surface phenomena of lipid-AMP interactions (Volinski et al, 2006).…”
Section: Antimicrobial Peptides: Monolayermentioning
confidence: 99%